PROMOSI AGROWISATA TENAYAN RAYA PEKANBARU - Dwi Juniar Putri Sitorus; Teguh Widodo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Promotion is something that is very useful in the marketing mix of a company in offering goods and services. This promotional activity not only serves as a means of communication between consumers and companies, but promotion also serves to persuade consumers to buy and use services according to what someone needs. Tenayan Raya Pekanbaru agro-tourism is an agro-tourism which has an educational tourism concept. This study aims to determine how the promotion at Agro-tourism Tenayan Raya Pekanbaru. This study uses a qualitative descriptive method to examine the problem under study by making three key informants as sources, namely owners, managers, and employees. While the data collection techniques in this study used interviews, observation, and documentation. Based on the results of the research that has been done, the overall results of the interview answers say that the promotion in Tenayan Raya Agro-tourism is quite good, but still needs to be improved. Keywords : Promotion, Agro-tourism, Tourism Objects.